2020
DOI: 10.2478/acve-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of HA and NA Genes of Swine Influenza Viruses in Serbia in 2016-2018

Abstract: Pigs are very important for the epidemiology of influenza A viruses, being commonly infected with the lineages of most adapted H1N1, H3N2, H1N2 swine subtypes. Epidemiological complexity of swine influenza is increasing by a periodic spillover of human or avian viruses in the pig population when genetic shifts can occur. The objectives of this research were to determine the presence of the influenza A virus in nasal and tracheobronchial swabs and lung tissue samples of ill and dead pigs on commercial farms, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Lysine at position 251 was described as a virulence factor in H1avN1 viruses (5). The possibly higher virulence of these two viruses could be associated with their having been detected in lung tissue samples of animals that died of swine influenza (27). Substitution D9N, which provides mitochondrial association of PB2 and consequently inhibition of expression of β-interferon and impaired immune response of the host (15) was not present in our isolates.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Lysine at position 251 was described as a virulence factor in H1avN1 viruses (5). The possibly higher virulence of these two viruses could be associated with their having been detected in lung tissue samples of animals that died of swine influenza (27). Substitution D9N, which provides mitochondrial association of PB2 and consequently inhibition of expression of β-interferon and impaired immune response of the host (15) was not present in our isolates.…”
Section: Discussionmentioning
confidence: 73%
“…Additional research in the form of an inhibition of haemagglutination test should be done to validate this assumption. Previous research on receptor-binding properties of these viruses revealed affinity to the α2-6 human type of receptors (27), indicating a major predisposition for transmission to human hosts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the odds for the initial detection of swIAV was lower in contact wipes compared to dust wipes and oral fluids in the nursery. Referring to tracheobronchial swabs, the burdensome sample procedure for animals and human as well as the low swIAV detection rate [ 53 ] disqualifies this type of sample as a tool for the detection of enzootically infected herds. However, tracheobronchial swabs might be suitable for detecting acutely diseased pigs as all tracheobronchial swabs positive samples in the nursery originated from pigs with clinical signs (data presented in [ 54 ]).…”
Section: Discussionmentioning
confidence: 99%